Experimental investigation of stability of water in oil emulsions at reservoir conditions: Effect of ion type, ion concentration, and system pressure. (1st May 2019) - Kazemzadeh, Yousef; Ismail, Ismail; Rezvani, Hosein; Sharifi, Mohammad; Riazi, Masoud
Graphical abstract: Highlights: Increasing salt concentration from 1000 to 10, 000 ppm helps the emulsion stability. Increasing pressure up to 4000 psi decreases the mean droplet area of water in oil. At high pressures, divalent cations form a more stable emulsion. Mg 2+ introduces a more stable emulsion than that of Ca 2+ . Abstract: Different ions present in formation water (FW) and aqueous phases injected into the oil reservoirs can affect the formation and stability of water-in-oil (W/O) emulsions. Previous studies regarding this issue devoted attention to the chemical compounds of the oil and water with a partial focus on different parameters at ambient pressure and temperature. However, pressure can multilaterally control the formation of emulsification phenomena. One important factor of emulsion stability is the asphaltene that is present in the crude oil. These particles are subjected to instability when they encounter a change in chemical composition and pressure, which affects the formation and stability of the emulsion. In this study, emulsification at various pressures and salinity were analyzed to determine the role of affecting factors, including asphaltene and various ions in the aqueous phase. The apparatus used for monitoring the emulsification was a HP-HT Emulsion Analyzer, designed and constructed by our research group. According to the results, the type and concentration of cations present in the aqueous phase govern the stability of the emulsion. At low salinities (i.e. up to 10, 000 ppm), the emulsion stability increases and then decreases with increasing salt concentration in the water phase. At high pressures (i.e. from 4000 to 6000 psi), divalent cations form a more stable emulsion in comparison with monovalent ones. In addition, among divalent cations, Mg 2+ introduces a more stable emulsion than that of Ca 2+ . Based on the results, the thermodynamic conditions affect the precipitation and deposition of asphaltene. Since dead oil was used in this research, the emulsion stability decreases with a decreasing asphaltene content at the interface at high pressures (i.e. 4000–6000 psi). This is due to the considerable reduction in the number of emulsifiers at the interface. Therefore, at high pressures, pressure increase reduces the emulsion stability. However, at low pressures (i.e. from 14.7 to 4000 psi), the increase in shear energy and asphaltene adsorption at the interface by ions overcomes the decrease in asphaltene due to its increased solubility. Therefore, at low pressures, pressure increase raises the emulsion stability.